2017
DOI: 10.1038/srep45827
|View full text |Cite
|
Sign up to set email alerts
|

Glycation of paraoxonase 1 by high glucose instigates endoplasmic reticulum stress to induce endothelial dysfunction in vivo

Abstract: High-density lipoprotein (HDL) modulates low-density lipoprotein and cell membrane oxidation through the action of paraoxonase-1 (PON1). Endoplasmic reticulum (ER) stress has been linked to a wide range of human pathologies including diabetes, obesity, and atherosclerosis. Previous studies have reported that PON1 is glycated in diabetes. The aim of this study is to investigate whether and how PON1 glycation contributes to endothelial dysfunction in diabetes. ER stress markers were monitored by western blot. En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…14,16,23 It has been reported that glycation of paraoxonase 1 by high glucose instigates ER stress to induce endothelial dysfunction, and glucolipotoxicity induces THP-1 monocyte apoptosis by up-regulating CHOP expression. 45,46 Our present experiments showed that gly-HDL induced ER stress, as demonstrated by the elevated nuclear translocation of ATF6, phosphorylation of PERK and eIF2α as well as up-regulation of GRP78 and CHOP, which was similar to the effects induced by TM. Conversely, gly-HDL-triggered apoptosis and activation of ER stress-CHOP pathway were suppressed by PBA (an ER stress inhibitor) and the gene silencing of PERK and CHOP.…”
Section: Discussionsupporting
confidence: 70%
“…14,16,23 It has been reported that glycation of paraoxonase 1 by high glucose instigates ER stress to induce endothelial dysfunction, and glucolipotoxicity induces THP-1 monocyte apoptosis by up-regulating CHOP expression. 45,46 Our present experiments showed that gly-HDL induced ER stress, as demonstrated by the elevated nuclear translocation of ATF6, phosphorylation of PERK and eIF2α as well as up-regulation of GRP78 and CHOP, which was similar to the effects induced by TM. Conversely, gly-HDL-triggered apoptosis and activation of ER stress-CHOP pathway were suppressed by PBA (an ER stress inhibitor) and the gene silencing of PERK and CHOP.…”
Section: Discussionsupporting
confidence: 70%
“…The effect of glycation on structure and functions of proteins has been widely investigated. Previous studies have shown that PON enzymes are sensitive to glycation triggered by glucose or methylglyoxal (MGO), which induces loss of biological activity [60][61][62]. Even oxidative stress could contribute to alterations of PON2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…When CHOP pathway was inhibited by quercetin, a natural flavonoid known to reduce ER stress, in HUVECs, endothelial function was restored [ 45 ]. Similar to in vitro studies, prolonged administration of PBA attenuated endothelial dysfunction in STZ-induced diabetic rats [ 46 ]. Choi et al [ 47 ] showed also that db / db type-2 diabetic mice had higher protein expression of ER stress markers: BiP, phosphorylated IRE-1α and its downstream XBP-1, phosphorylated PERK and its downstream phosphorylated elF-2α, compared to control animals [ 47 ].…”
Section: Er Stress and Endothelial Dysfunctionmentioning
confidence: 58%